Real-world evaluation of glucose-lowering therapies and the use of weight-adjusted variable rate intravenous insulin infusion in the management of hyperglycaemia in patients with acute coronary syndrome (REGULATE-ACS). (1st January 2023) - Liarakos, Alexandros Leonidas; Tran, Patrick; Keegan, Michelle; Robbins, Tim; Chaudhuri, Nadia; Murthy, Narasimha; Randeva, Harpal; Gholap, Nitin Narayan
Abstract: Introduction: Admission hyperglycaemia in acute coronary syndromes (ACS) is a strong independent predictor of adverse clinical outcomes post-ACS. We examined the safety, efficacy, and feasibility of a modified, weight-adjusted variable rate intravenous insulin infusion (VRIII) and evaluated current practice of prescribing novel cardio-protective glucose-lowering therapies in patients presenting with acute hyperglycaemia across the ACS spectrum. Methods: REGULATE-ACS was an observational single-centre study of consecutive patients admitted with acute hyperglycaemia post-ACS between 2020 and 2021. Following updated local guidance on a modified VRIII, we evaluated its safety and efficacy in glycaemic control, cardio-metabolic complications including hypoglycaemia (blood glucose <3 mmol/L) and 30-day mortality. We also determined the prescription of glucose-lowering therapies pre-discharge. Results: Out of 107 patients, mean age was 64.9 ± 12.2 years, 82% had known diabetes, and 15% newly diagnosed diabetes. 86.9% ( n  = 93) had an admission glucose ≥11 mmol/L. In patients treated with VRIII ( n  = 63/93, 67.7%), glucose improved from 17.5 to 9.0 mmol/L (IQR 7.1–12.1), which was 3 mmol/L lower ( p  = 0.03) than in patients not treated with VRIII ( n  = 30/93, 32.3%) where median glucose reduced from 12.6 to 12 mmol/L (IQR 8.6–13.9). No significant hypoglycaemia, arrhythmia or worsening pulmonary oedema associated with VRIII was found. Novel glucose-lowering therapies were initiated in 20/71 (28.2%) and 3/15 (20.0%) of patients with prior and newly diagnosed diabetes, respectively. Conclusion: This real-world analysis provides further support of efficacy, safety, and feasibility of a modified, weight-adjusted VRIII in managing acute hyperglycaemia in ACS. Despite established cardio-protective benefits of novel glucose-lowering therapies, <1/3 of eligible patients received such agents pre-discharge, demanding further research and awareness.